Global childhood unintentional injury surveillance in four cities in developing countries: a pilot study - Adnan A Hyder; David E Sugerman; Prasanthi Puvanachandra; Junaid Razzak; Hesham El-Sayed; Andres Isaza; Fazlur Rahman; Margie Peden (The World Health Organization, 2009)
OBJECTIVE: To determine the frequency and nature of childhood injuries and to explore the risk factors for such injuries in low-income countries by using emergency department (ED) surveillance data. METHODS: This pilot study represents the initial phase of a multi-country global childhood unintentional injury surveillance (GCUIS) project and was based on a sequential sample of children < 11 years of age of either gender who presented to selected EDs in Bangladesh, Colombia, Egypt and Pakistan over a 3-4 month period, which varied for each site, in 2007. FINDINGS: Of 1559 injured children across all sites, 1010 (65%) were male; 941 (60%) were aged > 5 years, 32 (2%) were < 1 year old. Injuries were especially frequent (34%) during the morning hours. They occurred in and around the home in 56% of the cases, outside while children played in 63% and during trips in 11%. Of all the injuries observed, 913 (56%) involved falls; 350 (22%), road traffic injuries; 210 (13%), burns; 66 (4%), poisoning; and 20 (1%), near drowning or drowning. Falls occurred most often from stairs or ladders; road traffic injuries most often involved pedestrians; the majority of burns were from hot liquids; poisonings typically involved medicines, and most drowning occurred in the home. The mean injury severity score was highest for near drowning or drowning (11), followed closely by road traffic injuries (10). There were 6 deaths, of which 2 resulted from drowning, 2 from falls and 2 from road traffic injuries. CONCLUSION: Hospitals in low-income countries bear a substantial burden of childhood injuries, and systematic surveillance is required to identify the epidemiological distribution of such injuries and understand their risk factors. Methodological standardization for surveillance across countries makes it possible to draw international comparisons and identify common issues.